Hemodialysis as a treatment option for chronic kidney disease in Ekiti State University Teaching Hospital: a retrospective study - Ibitoba, Funmilayo A.; Akpor, Oluwaseyi A.; Ogunkorode, Agatha O.; Bello, Aderemi Y.; Ogunyemi, Omotomilola O. (KIDNEYS, 2024)
The prevalence of chronic kidney disease (CKD) has surged to approximately 13 % in the past two decades due to an increase in associated risk factors. Poorly managed CKD can progress to end-stage renal disease, necessitating renal replacement therapy, with hemodialysis being the most common form. This study examines a 5-year record of hemodialysis in a healthcare facility in southwest Nigeria. Study data were collected from dialysis register and case study of patients that were consecutively dialyzed at the dialysis centre of Ekiti State University Teaching Hospital between January 2017 and December 2021. Unstructured proforma was used to extract data for the study. There was a total of 152 patients and 1600 hemodialysis sessions between January 2017 and December 2021. More than a quarter of the patients were civil servants and there were more males than females (p = 0.3325). CKD was the major indication for hemodialysis with hypertension as its main cause while post-partum hemorrhage was the most common cause of acute kidney injury. Only 3.3 % of the patients had permanent access of arteriovenous fistula. Notably, 47.2 % of the patients were lost to follow-up, 29.8 % left to other centres by either referral or self-decision, while 18.6 % died of CKD-related complications. Nevertheless, 4.4 % patients were still dialyzing in the Centre as of December 2021. Comparatively fewer hemodialysis sessions occurred, yet they led to improved patient outcomes. Regular follow-ups and government subsidies are recommended to ease patient burdens.